Atherogenic Indices in Type 2 Diabetic Iraqi Patients and Its Association with Cardiovascular Disease Risk - Hind Shakir Ahmed; Melak Saleh Mohammed (مجلة كلية الطب, 2023)
Background: Diabetes is a serious risk factor for atherosclerotic cardiovascular disease and an important cause of mortality. Dyslipidemia is commonly related to type 2 diabetes, and the atherogenic index of plasma is a strong marker to predict the risk of atherosclerosis and coronary heart disease.